Auto-Antibody Production During Experimental Atherosclerosis in ApoE-/- Mice - Hutchinson, Mark A.; Park, Han-Sol; Zanotti, Kimberly J.; Alvarez-Gonzalez, Juan; Zhang, Jing; Zhang, Li; Telljohann, Richard; Wang, Mingyi; Lakatta, Edward G.; Gearhart, Patricia J.; Maul, Robert W. (Frontiers in Immunology, 2021)
Current models stipulate that B cells and antibodies function during atherosclerosis in two distinct ways based on antibody isotype, where IgM is protective and IgG is inflammatory. To examine this model, we generated ApoE-/- Aid-/- mice, which are unable to produce IgG antibodies due to the absence of activation-induced deaminase (AID) but maintain high plasma cholesterol due to the absence of apolipoprotein E (APOE). We saw a dramatic decrease in plaque formation in ApoE-/- Aid-/- mice compared to ApoE-/- mice. Rigorous analysis of serum antibodies revealed both ApoE-/- and ApoE-/- Aid-/- mice had substantially elevated titers of IgM antibodies, suggesting a more complex dynamic than previously described. Analysis of antigen specificity demonstrated that ApoE-/- Aid-/- mice had elevated titers of antibodies specific to malondialdehyde-oxidized low density lipoprotein (MDA-oxLDL), which has been shown to block macrophage recruitment into plaques. Conversely, ApoE-/- mice showed low levels of MDA-oxLDL specificity, but had antibodies specific to numerous self-proteins. We provide evidence for a hierarchical order of antibody specificity, where elevated levels of MDA-oxLDL specific IgM antibodies inhibit plaque formation. If the level of MDA-oxLDL specific IgM is insufficient, self-reactive IgM and IgG antibodies are generated against debris within the necrotic environment of an arterial plaque, resulting in increased inflammation and further plaque expansion.